Implementasi Filsafat Pancasila dalam Pendidikan Masyarakat di PKBM Cendekia Kabupaten Batubara - Dinda Putri Ainiyah; Jesika Anastasya Sihotang; Mas Iren Anjelina Zebua; Sabrina Maharani Putri; Yahya Rambe; Yossy Meliana Ginting (Didakta Nusantara: Journal of Education and Learning, 2026)
Community education plays a strategic role in strengthening character development and civic awareness amidst rapid social transformation. As the philosophical foundation of the Indonesian nation, Pancasila provides fundamental values that guide educational practices toward the development of ethical, democratic, and socially responsible citizens. This study aims to analyze the implementation of Pancasila philosophical values within the community education system at PKBM Cendekia, Pahang Village, Talawi District, Batubara Regency. A qualitative descriptive approach was employed using observation, in-depth interviews, and documentation. The participants consisted of the PKBM head, tutors, and learning citizens involved in equivalency education programs. Data were analyzed through the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that Pancasila values are implemented through three main strategies: integration into learning activities, habituation of positive social behavior, and role modeling by tutors and institutional leaders. The values of divinity, humanity, unity, democracy, and social justice are reflected in educational practices, community participation, and learner empowerment activities. This study contributes conceptually by proposing a community-based model for implementing Pancasila values through non-formal education institutions, particularly PKBM, as a means of strengthening civic character and social empowerment.